Modifikasi Sistem Elektrik Feeding Compound Serta Penambahan Alat Pendeteksi Compound Minim Dan Compound Putus - Ariawn, Mochamad Youfal; Kuswantori, Ari (Prodi D3 Teknik Elektronika Politeknik Gajah Tunggal, 2024)
Bald tubeless scrap is a defect in the form of a hole (usually long) in the inner liner area due to a lack of compound bank material on the squeegee and tubeless parts. Production data for December 2022-February 2023 shows the result that there are 156 Pcs or 174 PPM of bald tubeless scrap. This is caused by the compound bank in the empty calender which can cause bald tubeless scrap.The method used in this research is a modification method, with the aim of solving existing problems by modifying the compound feeding system and adding broken compound detectors and minimal compound, they are made.The results of this research are the modification of the electric compound feeding system and the addition of minimal compound detectors and compound breaks. These results have an impact on the reduction of bald tubeless scrap by 117 Pcs of greentire or 174 PPM in April-June 2023.